The contract reforestation program policy issues and constraints - Magno, Francisco A. (Philippine Journal of Public Administration, 1994)
The Department of Environment and Natural Resources (DENR) reported a reversal of the growing trend of deforestation in the country in 1990. This came during the second year of the Contract Reforestation Program of DENR. This article discusses several policy constraints that impede the sustainability and effective implementation of this program, as follows: (1) lack of tenure rights in reforested lands; (2) lack of food security components in reforestation projects; (3) lack of community participation in reforestation planning; (4) intrusion of patronage criteria in the selection of contractors; and (5) weak administrative capacity of the forest bureaucracy. It thus recommends that: (1) tenure rights be guaranteed for the local people in state-sponsored reforestation projects; (2) livelihood activities and food security provisions be made integral components of reforestation plans; (3) local communities be organized for forest management; (4) access to forest rehabilitation and management rights be democratized and devolved to upland communities; and (5) forest bureaucracy be-strengthened as a regulatory and developmental agency.